EFL teachers’ experience for hard of hearing students in inclusive setting - Ni Nyoman Ari Ratnadi; Luh Diah Surya Adnyani (Universitas Islam Malang, 2023)
Teaching students with hard of hearing in a mainstream school challenges teachers, including English as a foreign language (EFL) teachers. This narrative inquiry study presents EFL teachers' experience teaching hard-of-hearing students in inclusive classrooms. Six EFL teachers participated and had in-depth interviews. The finding shows that EFL teachers are aware of hard-of-hearing students’ uniqueness. They facilitate them in learning English together with hearing students from the beginning of the lesson to the closing session. Teachers modify their teaching dan communication by combining spoken, written, sign language, and translation. Explaining and instruction to hard-of-hearing students are presented in slow and loud voices, emphasizing mouth movement and repetition. This study presents implications based on the teachers’ stories and suggestions for future study.